Identification of five hub immune genes and characterization of two immune subtypes of osteoarthritis - Pan, Lifeng; Yang, Feng; Cao, Xianhua; Zhao, Hongchang; Li, Jian; Zhang, Jinxi; Guo, Jiandong; Jin, Zhijiang; Guan, Zhongning; Zhou, Feng (Frontiers in Endocrinology, 2023)
Background: Osteoarthritis (OA) is one of the most prevalent chronic disease, leading to degeneration of joints, chronic pain and disability in the elderly. Little is known about the role of immune related genes (IRGs) and immune cells in OA. Method: Hub IRGs of OA were identified by differential expression analysis and filtered by three machine learning strategies, including random forest (RF), Least absolute shrinkage and selection operator (LASSO) and support vector machine (SVM). A diagnostic nomogram model was then constructed by using these hub IRGs, with receptor operator curve (ROC), decision curve analysis (DCA) and clinical impact curve analysis (CICA) estimating its performance and clinical impact. Hierarchical clustering analysis was then conducted by setting the hub IRGs as inputting information. Differences in immune cell infiltration and activities of immune pathways were reveled between different immune subtypes. Result: Five hub IRGs of OA were identified, including TNFSF11, SCD1, PGF, EDNRB and IL1R1. Of them, TNFSF11 and SCD1 contributed most to the diagnostic nomogram model with an AUC of 0.904 and 0.864 respectively. Two immune subtypes were characterized. The immune over-activated subtype showed excessively activated cellular immunity with higher proportion of activated B cell and activated CD8 T cell. The two phenotypes were also seen in two validation cohorts. Conclusion: The present study comprehensively investigated the role immune genes and immune cells in OA. Five hub IRGs and two immune subtypes were identified. These findings will provide novel insights for the diagnosis and treatment of OA.